AMERICAN QUAKERS AND THEIR PACIFIST ACTIVITY - E. V. Galkina (Гуманитарные и юридические исследования)
The article is devoted to the problems of American Quakers' activity in North America beginning with the 1660s. The analysis of their religious doctrine incorporating the elements pacifism is carried out. Both the compulsory theological components and the peaceful platform of Quakers' activity in America are specified. The issue of pacifism in Quakers' activities and the attitude of other religious movements and the state authories towards them are in the focus of consideration.